Ziisabaakodakaan: The Place Where Sugar is Made - Pine, Deborah Theresa (2017)
One of the most pressing environmental challenges facing people around the world is climate change. Climate change scientists have pointed out that in 100 years the maple trees will no longer produce sap for making maple syrup. Sugar Maple trees (Ninaatigoog) are not adapting to the warmer climate. There are cultural practices of the Anishinabek that revolve around participating and producing natural foods such as Ziiwaagamide that are dependent on the environment. This thesis looks to address the following questions through research conducted with a family based practice of the Ziisabaakodakaan in Wiigwaaskinigaa. What then will be the social and cultural impacts of the disappearance of Ziisabaakodakaan practices on Anishinabek well-being? How have changes of Ziisabaakodakaan practices influenced Anishinaabemowin? How can Anishinaabe Gkendaasowin assist Anishinabek in coping with ecological changes due to climate change? Anishinaabe knowledge is complex and vast and it gathered from a lifetime of observation and engagement on the land. The research findings suggest that Anishinaabe elders are witnessing, the poor health of Sugar Maple trees and this may influence cultural and community resiliency and thus adaptation to climate change. M.A.